Pengujian Kehandalan Jaringan Terhadap TCP/SYN Flood Attack Dan Penanganannya - Hartanto, Sri (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
TCP/SYN Flood Attack is a type of Denial of Service (DoS) attack. The TCP/SYN Flood Attack paralyzes the Web Server computer by flooding it with large amounts of data packets so that the communication network system becomes paralyzed. The TCP/SYN Flood Attack takes advantage of the weakness of the data transfer method between the Web Server computer and the client computer. To recognize how a TCP/SYN Flood Attack occurs on a Web Server computer, in this research, a simulation of a TCP/SYN Flood Attack attack was carried out on a Web Server computer from three client computers in a Local Area Network (LAN) network. Furthermore, every hour, the number of packets received by the Web Server computer and the performance of the Web Server computer before and after handling are observed. With this research, it is hoped that it will be known how the performance of telecommunication networks, in this case, Web Server computers, can handle TCP/SYN Flood Attacks both before and after firewall filters are applied.